Pengaruh Lingkungan Sekolah dan Motivasi Belajar Terhadap Hasil Belajar Siswa Setingkat Menengah Pertama - Firda Nuriyah; Farida Nabilah; Mufaizah Mufaizah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Student learning outcomes are a benchmark for achieving learning objectives in schools, but it is not uncommon for learning outcomes to be one of the problems that are often experienced in various school institutions. Learning problems and school demands cause anxiety, such as difficulty managing study time, anxiety of failing exams and grades below the standard are considered to be problems that are often found in schools. This study aims to determine how junior high school students' learning outcomes are influenced by the school environment and their learning motivation. This study combines literature study methodology with a qualitative approach. Books, journals, and articles relevant to the research topic are examples of research sources. The findings of the study indicate that learning motivation and the school environment have a significant impact on junior high school students' learning outcomes.